Multiple Cutaneous Metastases as Initial Presentation in Advanced Colon Cancer - Sudheer Nambiar; Asha Karippot (Case Reports in Gastrointestinal Medicine)
Skin metastases from advanced colorectal cancer are relatively rare and occur most often when the cancer is advanced, following the spread to other organs. Cutaneous metastases occur in about 3% of advanced colorectal cancers. We present an extremely rare case of a 68-year-old woman with advanced ascending colon adenocarcinoma that presented with multiple rapidly progressing painless cutaneous metastatic lesions with no other distant metastases. Of all the tumors, breast cancer most commonly spreads as cutaneous metastasis is followed by lung, colorectal, renal, ovarian, and bladder cancers. Cutaneous metastases can present in a variety of clinical manifestations, such as a rapidly growing painless dermal or subcutaneous nodule with intact overlying epidermis or as ulcers. In cases where the cutaneous deposit is isolated, as in visceral metastasis, there is a role for radical management such as wide local excision and reconstruction. In our patient, since she had multiple cutaneous metastases she began treatment with palliative systemic combination chemotherapy.